Book review of The Emotions Industry edited by Mira Moshe, New York: Nova Publishers, 2014, 265 pages - Nicoleta Corbu (Romanian Journal of Communications and Public Relations, 2015)
Book review of The Emotions Industry edited by Mira Moshe, New York: Nova Publishers, 2014, 265 pages